Insights Into Non-Alcoholic Fatty Liver Disease and Diabetes Mellitus in Somalia: Prevalence and Risk Factors - Jeele MOO; Mohamed HN; Addow ROB; Hassan MO; Adam BA (Diabetes, Metabolic Syndrome and Obesity)
Mohamed Osman Omar Jeele,1 Hawa Nuradin Mohamed,1 Rukia Omar Barei Addow,2 Mohamed Omar Hassan,3 Bakar Ali Adam4 1Department of Internal Medicine, Mogadishu Somali Turkish Training and Research Hospital, Mogadishu, Somalia; 2Department of Public Health, Horseed International University, Mogadishu, Somalia; 3Department of Cardiology, Mogadishu Somali Turkish Training and Research Hospital, Mogadishu, Somalia; 4Department of Neurology, Mogadishu Somali Turkish Training and Research Hospital, Mogadishu, SomaliaCorrespondence: Mohamed Osman Omar Jeele, Medical Doctor, Specialist in Internal Medicine, Mogadishu Somali Turkish Training and Research Hospital, Department of Internal Medicine, Mogadishu, Somalia, Tel +252615775226, Email drjeele@gmail.comIntroduction: NAFLD is a rapidly expanding global health issue that is distinguished by the accumulation of hepatic fat that is not associated with alcohol consumption. Parallel to the increase in obesity and type 2 diabetes mellitus (T2DM), its prevalence is also increasing. Amidst a backdrop of limited epidemiological data, Somalia, which is undergoing urbanization and dietary adjustments, is contending with escalating rates of NAFLD. Our study aims to addresses critical voids in local epidemiological data regarding this subject in Somalia.Methods and Materials: The objective of this retrospective study was to evaluate the prevalence of NAFLD and concomitant risk factors among T2DM patients at the Mogadishu Somalia Turkish Training and Research Hospital. A total of 832 patients diagnosed with T2DM between May 2023 and March 2024 were used to analyze the data. Various variables, such as age, sex, diabetic medications, hypertension, insulin resistance, hyperlipidemia, and NAFLD grade, were obtained from electronic medical records. Statistical analyses were conducted to investigate the associations and predictors of NAFLD using descriptive analysis, logistic regression, and multiple regression.Results: The study cohort was predominately female (57%), with a mean age of 53.48 years. The most prevalent grades of NAFLD were grade 1 and grade 2, with NAFLD being identified in 53.8% of patients. NAFLD displayed a robust correlation with insulin resistance (OR: 52.04), with hypertension (OR: 20.091) and hyperlipidemia (OR: 2.528) following shortly thereafter. These factors collectively account for 57% of the variance in NAFLD, as indicated by multiple regression analysis (R2 = 0.57, F (6,823) = 184.302, p < 0.001).Conclusion: This investigation emphasizes the presence of a high prevalence of NAFLD among T2DM patients in Mogadishu, Somalia, 53.8% which is substantially influenced by hypertension, insulin resistance, and hyperlipidemia. In this region, the necessity of targeted healthcare strategies to mitigate metabolic liver diseases is underscored by the results.Keywords: NAFLD, Type 2 diabetes mellitus, insulin resistance, hepatosteatosis, Somalia